Pengaruh Implementasi Metode Pembelajaran Learning Contract terhadap Pendidikan Karakter dan Kedisiplinan Siswa Kelas 5 Sekolah Dasar - Meytha Friska Olvianti; Jarmani Jarmani; Endang Supartin (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
This study aims to investigate the effect of learning contract implementation on character education and discipline of grade 5 elementary school students. The learning contract method is used to improve students' independence, responsibility and discipline in the learning process. The research was conducted by applying learning contract in learning in grade 5 elementary school and observing the changes in character education and students' discipline level after the implementation of this method. The results of the study are expected to provide a deeper understanding of the effect of the implementation of learning contract learning method on character education and discipline of grade 5 elementary school students. The implication of this study is expected to contribute to the development of more effective learning methods to improve character education and student discipline at the elementary school level.